2012
DOI: 10.1371/journal.pone.0037494
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Deception in Movement: The Case of the Side-Step in Rugby

Abstract: Although coordinated patterns of body movement can be used to communicate action intention, they can also be used to deceive. Often known as deceptive movements, these unpredictable patterns of body movement can give a competitive advantage to an attacker when trying to outwit a defender. In this particular study, we immersed novice and expert rugby players in an interactive virtual rugby environment to understand how the dynamics of deceptive body movement influence a defending player’s decisions about how an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
215
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(235 citation statements)
references
References 41 publications
16
215
4
Order By: Relevance
“…These effects were independent from the object weight. Providing exaggerated body-related cues that induce others to make incorrect action predictions and minimizing or delaying informative postural cues are fundamental aspects of effective deception (Brault et al 2010;Brault et al 2012). Here, we showed that these alterations of movement kinematics succeeded in blurring the observer's sensitivity in predicting object weight by observing reaching-to-grasp and lifting movements.…”
Section: Deceptive Intentions But Not Kinematic Adaptations Fool the mentioning
confidence: 71%
See 1 more Smart Citation
“…These effects were independent from the object weight. Providing exaggerated body-related cues that induce others to make incorrect action predictions and minimizing or delaying informative postural cues are fundamental aspects of effective deception (Brault et al 2010;Brault et al 2012). Here, we showed that these alterations of movement kinematics succeeded in blurring the observer's sensitivity in predicting object weight by observing reaching-to-grasp and lifting movements.…”
Section: Deceptive Intentions But Not Kinematic Adaptations Fool the mentioning
confidence: 71%
“…Conversely, the ANOVA performed on the lifting duration revealed a significant interaction between weight and action condition (F(2,30) = 4.77, P = 0.016, η P 2 = 0.241), because the truthful lifting of heavy objects lasted less than the lifting in all other types of videos (all P < 0.048). Thus, the lifting of heavy objects was delayed for both deceptive and deceived actions as compared to truthful lifting movements, suggesting that, even if this temporal kinematics parameter can be intentionally altered by deceptive intentions (Brault et al 2012;Tidoni et al 2013), it cannot dissociate between intentional deception and kinematics adjustment behavior (Fig. 2).…”
Section: Kinematics Analysismentioning
confidence: 99%
“…This highlights the importance of the unfolding pattern of the attacker's movements in informing and guiding choices about when and how to act in an anticipatory way (Brault et al, 2012).…”
Section: Action Anticipation Through Its Sound Alone 23 23mentioning
confidence: 99%
“…Through these mechanisms it is hypothesised that expert sports players are better able to predict whether a basketball shot will result in a basket (Aglioti, Cesari, Romani, & Urgesi, 2008), detect when an attacker is trying to use his/her movements to deceive an opponent in rugby (Brault et al, 2012) and to anticipate deceptive action in soccer (Tomeo, Cesari, Aglioti, & Urgesi, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation